The Use of Spinning Wheel Games to Improve Students’ Writing Procedural Texts - Rachmaida, Fahria; Mutiarani, Mutiarani (JOLLT Journal of Languages and Language Teaching, 2022)
Most of the students’ ability to write in English is still poor. Their text contains many errors in content, organization, and use of language. Students find it difficult to explain their ideas in written form, and students lack vocabulary, which can make it difficult to choose words to group into good writing. some teachers still find it difficult to apply media during learning this makes the class atmosphere less lively and makes them bored. the purpose of this research is to find out whether utilizing Spinning Wheel is effective or not in improving studentsâ€™ writing Procedure Text. The method used in this research is descriptive research. I found a solution by describing the problem qualitatively. The end result is a game that imitates the Spinning Wheel Game while teaching English writing techniques that can increase students’ interest, challenge their thinking and enable them to produce procedural texts while playing. The spinning wheel was used after the researcher explained the material about the procedure text. Students are asked to make groups and each group gets a different theme. themes are randomized with spinning wheel games by web wheelofnames.com. Therefore, the game is one of the tools that can be used in learning English, there are many learning media for learning writing skills. One game that can be used is Spinning Wheel. By using games students can learn to write procedure texts in a fun and interesting way. The spinning wheel game can be chosen as a tool for students to write procedure texts correctly and clearly. This game has been evaluated by several researchers and high school students. This game is very helpful in learning to write procedure text. These games can make students challenge their way of thinking, fun and enjoyable.